Maintaining Inter-religious Harmony through Acculturation of the Local Tradition in the Dani Muslim Community, Papua - Ahmad Syarif Makatita; Natasya Aulia Husain; Abdul Aziz Harahap (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2022)
This study aims to identify patterns of social interaction among the inter-religious communities in Jayawijaya, Papua, through the tradition of Bakar Batu. This study employs a qualitative approach by interpreting data from observation and interviews. Associative and dissociative social interaction patterns are also used as analytical theories. This study revealed that the associative interaction pattern is evident in the social interaction between the Dani Muslim community and the Christian community in the Bakar Batu tradition through accommodation and acculturation. The accommodation process is reflected in the form of tolerance; both respect each other despite their different religious teachings. Meanwhile, the acculturation process is found in reconstructing the essential elements in the practice of the Bakar Batu tradition by substituting pork with halal meat. The theoretical implication of this study reveals that associative patterns of social interaction can be the basis for paradigms and approaches to harmonizing relations among distinct religious communities and between religion and culture. However, this study has not discussed the role of Islamic socio-religious institutions or organizations in the practice of the Bakar Batu tradition.